2022
DOI: 10.1007/s00418-022-02154-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord from body donors is suitable for multicolor immunofluorescence

Abstract: Immunohistochemistry is a powerful tool for studying neuronal tissue from humans at the molecular level. Obtaining fresh neuronal tissue from human organ donors is difficult and sometimes impossible. In anatomical body donations, neuronal tissue is dedicated to research purposes and because of its easier availability, it may be an alternative source for research. In this study, we harvested spinal cord from a single organ donor 2 h (h) postmortem and spinal cord from body donors 24, 48, and 72 h postmortem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…It was not possible to limit counts to α-motoneurons, because ChAT signals were too weak in some donor nerves due to the postmortem interval (interval between the time of death of individuals and tissue fixation). This is in accordance with a recent study where we have demonstrated that the ChAT signal is stable for 24 h after death and then decreases [ 19 ]. The TA branch showed 1597.14 ± 325.94 myelinated fibers ( Table 1 ).…”
Section: Resultssupporting
confidence: 94%
“…It was not possible to limit counts to α-motoneurons, because ChAT signals were too weak in some donor nerves due to the postmortem interval (interval between the time of death of individuals and tissue fixation). This is in accordance with a recent study where we have demonstrated that the ChAT signal is stable for 24 h after death and then decreases [ 19 ]. The TA branch showed 1597.14 ± 325.94 myelinated fibers ( Table 1 ).…”
Section: Resultssupporting
confidence: 94%
“…The question therefore remains: What is the allowable interval between death and tissue fixation to provide adequate samples for research purposes, especially those requiring immunohistochemistry? Reissig et al ( 2022 ) have now undertaken such a rigorous immunohistochemical study using human body donor spinal cord samples received 24 h, 48 h, and 72 h postmortem. The tissue immunostaining results from these samples were compared to those from a “control” sample organ donor received 2 h postmortem.…”
Section: Body Donor Tissues For Clinical and Basic Research Studiesmentioning
confidence: 99%